2017
DOI: 10.1002/pi.5424
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly swellable hydrogels of water-soluble carboxymethyl chitosan and poly(ethylene glycol)

Abstract: Highly swellable hydrogels were produced by crosslinking of high molecular weight carboxymethylated chitosan (CmCHT) with poly(ethylene glycol) (PEG) oligomers. The hydrogel swelling capacity could be controlled via the crosslinking density and ranged from 900% to 5600%. The hydrogels showed good homogeneity with a high interconnected porosity in the swollen state and with nanodomains rich in CmCHT and others rich in PEG diglycidyl ether. Oscillatory frequency sweep analysis showed a storage modulus of 27 kPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Gámiz-González et al. 21 also reported that the swelling ratio of the CMCht hydrogel scaffolds decreased as the PEGDE concentration increased.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Gámiz-González et al. 21 also reported that the swelling ratio of the CMCht hydrogel scaffolds decreased as the PEGDE concentration increased.…”
Section: Resultsmentioning
confidence: 92%
“…It was seen that after cross-linking at 40°C overnight, liquid CMCht-SF solutions were converted to gel state through the ring-opening reaction of the epoxy groups in PEGDE with the amine and hydroxyl groups in carboxymethyl chitosan. 13,21…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IIR FTIR spectra showed that the absorption area of the -OH group was widening; this indicates the increasing number of hydrogen interactions that made the vibration of the -OH group weaker [17]. In the IIM the CS group wave number (702.9 cm -1 ) also shifted to a larger wavenumber (848.68 cm -1 ), this is likely due to the presence of PEGDE as a crosslinker agent and PVA as a plasticizer on the membrane that experience interaction with PEATM-Au which influences the shift of vibrational wavenumber of CS bonds [17][18]. Based on the plank equation theory, which is the basis in the FTIR analysis, explains that energy is directly proportional to the wavenumber (E = h ѵ), the greater the vibrational energy, the greater the peak of the wavenumber [19].…”
Section: Characterization Of Iim Ftirmentioning
confidence: 99%